IDENTIFICACIÓN DE DELECIONES EN AFECTADOS DE DISTROFIA MUSCULAR DE DUCHENNE Y BECKER (DMD/DMB) Y DIAGNÓSTICO DE PORTADORAS POR METODOLOGÍAS MOLECULARES - Hernández Rodríguez, Patricia; Departamento de Biología Facultad de Ciencias Pontificia Universidad Javeriana (2013)
A rehearsal of multiplex PCR (Polymerase chain reaction), was designed (6-plex) that amplifies 6 exons (51, 48, 45, 43, 19, 8) of the Dystrophin gene simultaneously, these exons is that present high mutations frequency. The deletions proportion observed in this study by means of the system 6-plex corresponded to 31,25%, almost al! the detected deletions 60% in volved the exons 44 at 52. With the propase of identifying carriers women of DMD and DMB it was used dosage gene, through this methodology 7 women carriers and 15 were identified as not carries deletions for the analyzed exons, in this study was not any woman carrier duplication. With the use dinucleotide polymorphyisms (CA)n located inside the gene was possible to establish inforrnation on X chromosome that possibly this affected in 63% ofthe analyzed women.